EXPERIMENTAL MEASUREMENTS BY VARIOUS INSTRUMENTATIONS TO ANALYSE DATA FOR MODELLING DPM CONCENTRATIONS IN UNDERGROUND MINES - Magauiya, Nursultan (Nazarbayev University School of Mining and Geosciences, 2022)
During underground mining operations, the ventilation system provides fresh air to reduce the impact of diesel engine exhaust gasses. Most dangerously, diesel particulate matter (DPM), is known to be a cancer - causing factor when inhaled for a sustained length of time in these diesel-powered vehicles. This problem is widespread in the mining industry, also in Kazakhstan. Diagnostic and monitoring technologies for DPM in the mining sector are still in their development stage, as well as approaches for detecting DPM in underground mines. The main objective of this thesis is to conduct experimental measurements by various instrumentations to analyze data for modelling DPM concentrations in underground mines. In order to achieve this goal, the existing literature is reviewed, and the methodology from these studies was modified in accordance with the measurements, that were done in the underground mine of Eastern Kazakhstan region. From the measurements, the data of airflow velocity, particulate matters, black carbon concentration, lung deposited surface area concentration, and particle diameters were obtained. The measuring instruments are anemometer, RizgardPM, Microaeth, and Partector. From these instruments the velocity, different Particulate Matter (PM1, PM2.5, and PM10), black carbon concentration, and lung-disposal surface area values were received, accordingly. The results from these tools were analyzed based on correlation factors. The ANSYS CFD software were used to simulate the velocity for this thesis. Initially, the data was analyzed for modeling purposes and were taken using equipment from underground measurements. In addition, the geometry of the mine was created in accordance with mine surveyor data and laser measurements directly from the underground mine. As a result, the preliminary velocity simulation is done.
Keywords: Type of access: Open Access; Research Subject Categories::TECHNOLOGY; underground mining; diesel particulate matter; DPM; Particulate Matter; anemometer; ANSYS CFD software